THU0515 PAIN IS THE MAIN DETERMINANT OF WELL-BEING IN OLIGO- AND POLYARTICULAR JIA: EVIDENCE FROM THE PHARMACHILD REGISTRY. (June 2019) - Alongi, Alessandra; Consolaro, Alessandro; Giancane, Gabriella; Magnolia, Maria Greca; Filocamo, Giovanni; Hoppenreijs, Esther; Ravelli, Angelo; Ruperto, Nicolino
Abstract : Background: Juvenile idiopathic arthritis (JIA) affects patients' well-being as the result of a complex interplay of multiple factors, including disease activity, symptoms, physical and emotional quality of life, and treatment burden. Little evidence exists about the relative contribution of these elements to disease impact. Objectives: 1) To identify direct and indirect determinants of well-being, expressed by VAS-measured patient/parent global assessment of well-being (PGW), in children with oligo- and polyarthritis. 2) To assess whether the impact of the major determinants varies with level of disease activity. Methods: We analyzed data of 1873 patients evaluated in 4464 prospective visits from the international JIA pharmacovigilance registry Pharmachild. Patient-reported outcomes were collected through the Juvenile Arthritis Multidimensional Assessment Report (JAMAR). Evaluated predictors of PGW included VAS-measured physician global assessment, inflammatory markers, active joint count, VAS-measured pain, morning stiffness duration, Juvenile Arthritis Functional Score (JAFS), Physical (PhHS) and Psychosocial (PsHS) subscales of the Pediatric Rheumatology Quality of Life (PRQL) scale, disease damage measured through the Juvenile Arthritis Damage Index (JADI) and adverse events (AE). We used path analysis to assess direct and indirect effects of variables on PWG. We repeated the analysis on subsets of visits stratified by disease activity, measured with JADAS10, to test differences across activity states. Results: Pain severity proved the strongest direct determinant of PGW (b 0.521, p<0.001), followed by Psychosocial (b 0.191, p<0.001) and Physical Health (b 0.158, p<0.001). Stiffness (f2 0.047, p<0.001) and joint damage by the JADI (f2 0.025, p<0.001) were also indirectly associated with PGW, through their effects on function and PhHS. Patient-reported adverse events (AE) had a small effect on PGW (f2 0.025, p<0.001) through their impact on PsHS. Relations among variables and relative coefficients are depicted in the graph. Multi-group comparison between Remission, Low (LDA), Moderate (MDA) and High Disease Activity (HDA) groups revealed that for subjects in Remission, pain had a lower impact on function and physical health compared to those with LDA, while remaining the strongest predictor of PGW. Among the HDA group, the direct effect of pain on well-being and the impact of physical health on psychosocial health was greater than in other activity states (table). The effect of AE remained significant across all activity categories. Conclusion: : Pain was the main determinant of PGW in all disease activity states. The level of PGW also reflected other aspects of disease impact, particularly physical and psychosocial distress, and, to a lesser extent, treatment adverse events. The impact of pain and physical functioning on psychosocial health and well-being varies with disease activity, being greater in patients with higher disease activity.  Reference: [1] Moorthy et al, Pediatric Rheumatology 2010; 8:20 Acknowledgement: for the Paediatric Rheumatology International Trials Organisation (PRINTO) Disclosure of Interests: Alessandra Alongi: None declared, Alessandro Consolaro Grant/research support from: AbbVie, Pfizer, Gabriella Giancane: None declared, Maria Greca Magnolia: None declared, Giovanni Filocamo: None declared, Esther Hoppenreijs: None declared, Angelo Ravelli Grant/research support from: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche, Consultant for: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche, Speakers bureau: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche, Nicolino Ruperto Grant/research support from: The Gaslini Hospital, where NR works as full-time public employee, has received contributions (> 10.000 USD each) from the following industries in the last 3 years: BMS, Eli-Lilly, GlaxoSmithKline, F Hoffmann-La Roche, Janssen, Novartis, Pfizer, Sobi. This funding has been reinvested for the research activities of the hospital in a fully independent manner, without any commitment with third parties., Consultant for: Received honoraria for consultancies or speaker bureaus (< 10.000 USD each) from the following pharmaceutical companies in the past 3 years: Ablynx, AbbVie, Astrazeneca-Medimmune, Biogen, Boehringer, Bristol-Myers Squibb, Eli-Lilly, EMD Serono, GlaxoSmithKline, Hoffmann-La Roche, Janssen, Merck, Novartis, Pfizer, R-Pharma, SanofiServier, Sinergie, Sobi and Takeda., Speakers bureau: Received honoraria for consultancies or speaker bureaus (< 10.000 USD each) from the following pharmaceutical companies in the past 3 years: Ablynx, AbbVie, Astrazeneca-Medimmune, Biogen, Boehringer, Bristol-Myers Squibb, Eli-Lilly, EMD Serono, GlaxoSmithKline, Hoffmann-La Roche, Janssen, Merck, Novartis, Pfizer, R-Pharma, SanofiServier, Sinergie, Sobi and Takeda.